“The system is obviously bonkers”: The APC Trap and the bind of scholarly publishing across four research intensive institutions in the U.S. - Melissa H. Cantrell; Rachel Caldwell; Jennifer A. Mezick; Matthew Estill; Lauren B. Collister (PLoS ONE, 2026)
This study analyzes the cognitive dissonance displayed by authors at research intensive institutions in the United States (U.S.) regarding the scholarly publishing of Open Access (OA) publications. A qualitative analysis of 154 open-ended responses was conducted. Eight codes were identified, then each response was analyzed for the codes. The codes themselves coalesce around a phenomenon the authors of this study term the article processing charge (APC) Trap, in which privileged and well-resourced researchers in the U.S. experience highly contradictory sentiments about OA publishing. The cognitive dissonance characteristic of the APC Trap result in strong feelings of conflict as well as powerlessness. The qualitative analysis reveals the APC Trap as a deeply layered phenomenon, with manifestation dependent on positionality, including demographic features and interactions between APC Trap codes. While much has been made of the failings of the APC model of OA publishing for under-resourced researchers, this study reveals the ways this publishing model is unsustainable even for privileged researchers most well-positioned to participate.